2018
DOI: 10.1371/journal.pgen.1007424
|View full text |Cite
|
Sign up to set email alerts
|

New insights into donor directionality of mating-type switching in Schizosaccharomyces pombe

Abstract: Mating-type switching in Schizosaccharomyces pombe entails programmed gene conversion events regulated by DNA replication, heterochromatin, and the HP1-like chromodomain protein Swi6. The whole mechanism remains to be fully understood. Using a gene deletion library, we screened ~ 3400 mutants for defects in the donor selection step where a heterochromatic locus, mat2-P or mat3-M, is chosen to convert the expressed mat1 locus. By measuring the biases in mat1 content that result from faulty directionality, we id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(48 citation statements)
references
References 99 publications
(130 reference statements)
6
41
0
1
Order By: Relevance
“…In this procedure, spores, but not vegetative cells, are stained dark by iodine vapors ( 31 ). Because heterochromatin is required for efficient mating-type switching and thus for homothallic mating and sporulation ( 22 , 32 , 33 ), the Δ K mutant epitype with established heterochromatin forms brown colonies similar to wild-type ( h 90 ) strains, while the Δ K mutant epitype lacking heterochromatin forms light mottled colonies like clr4 Δ strains ( 29 , 30 ). We found that in a Δ K mutant lacking both boundaries the dark epitype could not be readily propagated ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In this procedure, spores, but not vegetative cells, are stained dark by iodine vapors ( 31 ). Because heterochromatin is required for efficient mating-type switching and thus for homothallic mating and sporulation ( 22 , 32 , 33 ), the Δ K mutant epitype with established heterochromatin forms brown colonies similar to wild-type ( h 90 ) strains, while the Δ K mutant epitype lacking heterochromatin forms light mottled colonies like clr4 Δ strains ( 29 , 30 ). We found that in a Δ K mutant lacking both boundaries the dark epitype could not be readily propagated ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Three genetic screens have produced S. pombe mutants with donor choice defects (Egel et al 1984 ; Thon et al 2005 ; Maki et al 2018 ). Donor choice, or directionality of mating-type switching, refers to a selection process, whereby the mat2-P cassette is preferentially chosen in M cells to convert the expressed mat1 locus, while the mat3-M cassette is preferentially chosen in P cells, resulting in equal proportions of the two cell types (Fig.…”
Section: Chromatin Factors Required For Directional Mating-type Switcmentioning
confidence: 99%
“…Another strategy identified the multi-subunit Clr4-containing complex (CLRC) responsible for the methylation of histone H3K9 as necessary for proper donor choice, by searching for mutations that reduce heterologous switching in the wild-type h 90 strain but increase heterologous switching in the h 09 strain, where the mat2 and mat3 cassette contents are swapped (Thon et al 2005 ). More recently, we used a sensitive high-throughput fluorescence microscopy approach to find mutants with aberrant ratios of P and M cells, among which directionality mutants were identified (Maki et al 2018 ). Table 1 presents the mutants obtained in this screen that have defects in histone-modifying enzymes.…”
Section: Chromatin Factors Required For Directional Mating-type Switcmentioning
confidence: 99%
“…In all cases studied so far, it implies a genomic DNA rearrangement of the mating-type locus ( MAT , encoding the key regulators of sexual identity) and species have evolved very different molecular pathways for the same aim. In the fission yeast Schizosaccharomyces pombe , an imprint at mat1 (it is unknown whether the imprint is an epigenetic mark or a single nick) is introduced, that leads to a DSB during DNA replication [ 7 , 8 ]. Repair occurs with one of the two silent copies of mat1 , called mat2 and mat3 .…”
Section: Introductionmentioning
confidence: 99%